2014
DOI: 10.1117/1.jbo.19.8.086003
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dots targeted to vascular endothelial growth factor receptor 2 as a contrast agent for the detection of colorectal cancer

Abstract: Abstract. We successfully labeled colorectal cancer in vivo using quantum dots targeted to vascular endothelial growth factor receptor 2 (VEGFR2). Quantum dots with emission centered at 655 nm were bioconjugated to anti-VEGFR2 antibodies through streptavidin/biotin linking. The resulting QD655-VEGFR2 contrast agent was applied in vivo to the colon of azoxymethane (AOM) treated mice via lavage and allowed to incubate. The colons were then excised, cut longitudinally, opened to expose the lumen, and imaged en fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…38 In another study, Carbary-Ganz et al 39 successfully labeled CRC in vivo using QDs targeted to VEGFR2. QDs with emission centered at 655 nm were bioconjugated to anti-VEGFR2 antibodies through streptavidin/biotin linking.…”
Section: Applications Of Quantum Dotsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 In another study, Carbary-Ganz et al 39 successfully labeled CRC in vivo using QDs targeted to VEGFR2. QDs with emission centered at 655 nm were bioconjugated to anti-VEGFR2 antibodies through streptavidin/biotin linking.…”
Section: Applications Of Quantum Dotsmentioning
confidence: 99%
“…QDs with emission centered at 655 nm were bioconjugated to anti-VEGFR2 antibodies through streptavidin/biotin linking. 39 The resulting QD655-VEGFR2 contrast agent was functional in vivo and localized to the colon of azoxymethane-treated mice following lavage and incubation. This QD655-VEGFR2 contrast agent significantly enhanced the contrast between diseased and normal tissues.…”
Section: Applications Of Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48] Recently, our group demonstrated that QDot655 targeted to VEGFR2 (QD655-VEGFR2) can be applied to the colon of carcinogen-treated mice in vivo and provides significantly increased contrast between diseased and undiseased tissue ex vivo (explanted) with high sensitivity and specificity compared to a control contrast agent. 49 This quantum dot is readily available, easy to conjugate, emits in a region of light that has less endogenous emission interference, and is compatible with all commonly used optical coherence tomography (OCT) systems. Thus, evidence exists that quantum dots bioconjugated to VEGFR2 antibodies can provide a mechanism for evaluating the molecular changes of colorectal tumors in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that QD655-VEGFR2 can be used to label adenoma expressing VEGFR2 through in vivo labeling and ex vivo fluorescence imaging with high sensitivity and specificity, and also using the OCT/LIF microendoscope ex vivo. 49 Quantum dot fluorescence in the colon should coordinate with VEGFR2 expressing adenoma. OCT provided the gold standard for the presence of adenoma with immunohistochemistry (IHC) as a gold standard for VEGFR2 expression.…”
Section: Introductionmentioning
confidence: 99%